Procurement of medical equipment in Sweden - Terio, Heikki (Zdravniški vestnik, 2010)
In many hospitals in Sweden the importance of technology management is alreadyaccepted and accepted since the hospital managements have recognised that technology is an integral part of all major policy and planning decisions. Todayćs medical devices are technically complex and sometimes a system of interacting devices is required to achieve the desired clinical function. If the hospitals want to use the latest, modern technology, then they need to make substantial investments in both equipment and competence. Complex technology, large investments and need of highly qualifi ed personnel to handle the medical devices are factors that indicate a need of well-defi ned procurement process as an essential part of the total health technology management system that should be used in a hospital. In such a procurement process, carefully prepared planning of technology investments can reduce the running costs and costs for maintenance substantially. In addition, a well-defi ned procurement process contributes to increase the patient safety. In Karolinska University Hospital goods and services are purchased for more than 20% of the hospitalćs 1.2 billion turnover. It is therefore very important that the procurement is carried out eff ectively.
Keywords: Equipment And Supplies, Hospital; health care; Health Care Costs; Investments; medicinska oprema; nabava; Oprema in preskrba, bolnišnica; purchasing; Sweden; Švedska; Technology, Medical; Tehnologija medicinska; Vlaganje; Zdravstveno varstvo, stroški; zdravstvo